2019
DOI: 10.1152/japplphysiol.00629.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin improves endothelial function in patients with cystic fibrosis

Abstract: Cystic fibrosis (CF) is a genetic disorder associated with vascular endothelial dysfunction. Nitric oxide (NO) plays a major role in maintaining vascular function, and tetrahydrobiopterin (BH4) is a critical determinant of NO bioavailability. Thus the purpose of this study was to investigate the effects of oral administration of BH4 on endothelial function in patients with CF. Twenty-nine patients with CF (18 ± 8 yr old) and 29 healthy matched controls were recruited. Patients with CF participated in a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In a double-blind multicenter clinical trial 40 patients with cirrhosis and portal hypertension either received sapropterin (5 mg/kg/d for two weeks) or placebo, but hepatic blood flow, systemic hemodynamics, endothelial dysfunction markers, and liver function tests remained unchanged [238]. Other small cohort trials reported that a single oral dose of 10–20 mg/kg/d BH 4 improves endothelial function in patients with cystic fibrosis or healthy subjects (58 subjects) [239], 12 patients with systemic sclerosis [240] and 33 patients with rheumatoid arthritis [241], just to mention some of them. Supra-nutritional doses of folate seem to prevent and help to control diabetic complications [242].…”
Section: Other State-of-the-art and Future Therapeutic Strategies mentioning
confidence: 99%
“…In a double-blind multicenter clinical trial 40 patients with cirrhosis and portal hypertension either received sapropterin (5 mg/kg/d for two weeks) or placebo, but hepatic blood flow, systemic hemodynamics, endothelial dysfunction markers, and liver function tests remained unchanged [238]. Other small cohort trials reported that a single oral dose of 10–20 mg/kg/d BH 4 improves endothelial function in patients with cystic fibrosis or healthy subjects (58 subjects) [239], 12 patients with systemic sclerosis [240] and 33 patients with rheumatoid arthritis [241], just to mention some of them. Supra-nutritional doses of folate seem to prevent and help to control diabetic complications [242].…”
Section: Other State-of-the-art and Future Therapeutic Strategies mentioning
confidence: 99%
“…In the same study, a positive relationship between microvascular function and lung function was found suggesting that disease severity may contribute, at least in part, to microvascular dysfunction [ 34 ]. In follow-up studies, the same group demonstrated that four weeks treatment with sildenafil (an inhibitor of phosphodiesterase 5 that enhances NO metabolism) [ 35 ] and tetrahydrobiopterin (BH 4 , a determinant of NO bioavailability) [ 36 ] increased FMD in patients with CF. In vitro treatment of human umbilical vein endothelial cells (HUVEC) with CFTR inhibitor suppressed insulin-induced NO generation, by inhibiting eNOS and AKT activation/phosphorylation [ 37 ].…”
Section: Vascular Tonementioning
confidence: 85%
“…Stimulated superoxide production was significantly lower in ECs pre-incubated with plasma from patients with CF treated with BH 4 compared to ECs treated with pre-treatment plasma [ 36 ]. In an in vitro system using HUVEC, decreased CFTR expression led to increased oxidative stress ( Fig.…”
Section: Oxidative Stressmentioning
confidence: 87%
“…In CF, defective flowmediated dilation (FMD) of the brachial artery suggests NO bioavailability is reduced in response to shear stress (Poore et al, 2013), and improved by agents that increase NO availability (Rodriguez-Miguelez et al, 2018). This notion is further supported by the observation that acute supplementation with 20 mg/kg of oral tetrahydrobiopterin (an essential cofactor for eNOS activity) significantly improved FMD, through reduced superoxide production and increased NO, which is indicative of improved eNOS coupling in people with CF (Jeong et al, 2018).…”
Section: Introductionmentioning
confidence: 93%